Investigating the intention to use technology among medical students: An application of an extended model of the theory of planned behavior. Issue 2 (16th September 2020) - Arkorful, Vincent Ekow; Hammond, Anastasia; Lugu, Benjamin Kweku; Basiru, Ibrahim; Sunguh, Kenneth Khavwandiza; Charmaine‐Kwade, Priscilla
Abstract : Though the integration of technology into the health sector has been touted as one of the conduits for enhancing efficiency and effectiveness in health and service delivery, research reports of not only a slow pace of adoption, but also medical practitioner's negative tendency regarding technology adoption. Considering that medical students are likely to constitute the future work force to use technology for enhancing accuracy in medical decisions, their intention to use technology constitutes a cardinal factor for guiding the implementation of technology‐based initiatives in healthcare settings. By integrating descriptive norm, the study seeks to extend the theory of planned behavior (TPB) to investigate correlates of prospective users' behavioral characteristics relative to technology adoption. A field survey is conducted with 322 medical students from different medical schools undertaking mandatory clinicals in health facilities in Ghana. The structural equation modeling analysis of collected data revealed that, attitude, subjective norm, perceived behavioral control, and descriptive norm, all have significant positive relationship with student's technology adoption intention. The results of data analysis further revealed that, the core TPB constructs contributed 26% of the variance in technology adoption intention whiles the extended variable contributed to increasing the explanation of variance in student's adoption intention to 33%. Hence, the inclusion of descriptive norm increased the explained variance by 7% (Δ R 2 = 7%, p < .001). The results confirm the predictive potential and appropriateness of the TPB model. Arising from the empirical results, study implications are discussed.